2019
DOI: 10.1177/1362361319877329
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination in young adults with autism spectrum disorder

Abstract: This study examined rates of and contributing factors to self-determination among young adults with autism spectrum disorder. Caregivers of young adults with autism spectrum disorder, 16–25 years, from five Autism Treatment Network sites completed surveys about their young adults’ transition experiences including the American Institutes for Research Self-Determination measure. Data were analyzed using univariate and multivariate analysis. Caregivers ( n = 479) reported their young adults with autism spectrum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…Our findings provide evidence for ways to better support decision-making in autistic adolescents and to promote positive psychological and behavioural outcomes in them. In previous studies, parents of autistic youth report low decision-making capacity in their children (Cheak-Zamora, Maurer-Batjer, Malow, & Coleman, 2019), and autistic people self-report avoidance in making decisions (Luke et al, 2012). However, our results revealed that, at least in an experimental task, autistic adolescents have the capacity to make decisions comparable to those of their TD peers.…”
Section: Discussioncontrasting
confidence: 54%
“…Our findings provide evidence for ways to better support decision-making in autistic adolescents and to promote positive psychological and behavioural outcomes in them. In previous studies, parents of autistic youth report low decision-making capacity in their children (Cheak-Zamora, Maurer-Batjer, Malow, & Coleman, 2019), and autistic people self-report avoidance in making decisions (Luke et al, 2012). However, our results revealed that, at least in an experimental task, autistic adolescents have the capacity to make decisions comparable to those of their TD peers.…”
Section: Discussioncontrasting
confidence: 54%
“…Researchers (e.g. Carter et al., 2013; Cheak-Zamora et al., 2020) have gathered data from parents or carers to assess self-determination of autistic adolescents and adults. A number of others have utilized social skill programs and interventions to increase the self-determination of adolescents and adults (Fullerton & Coyne, 1999; Held et al., 2004), although these have not assessed ways in which the individual has demonstrated self-determination prior to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The results encourage further exploration of the scale’s validity in both populations (people with intellectual disability and people with SMD), and they also stimulate research in other populations (e.g., people with autism spectrum disorder or people with other special needs). Recent investigations have reported lower levels of self-determination in people with autism spectrum disorder (Cheak-Zamora et al, 2020; Chou et al, 2017), with self-determination and social inclusion identified as priority areas for intervention and research (Morán et al, 2019). Furthermore, the AUTODDIS scale will be useful for researchers who wish to ensure that the scale is effective in estimating the impact of practices aimed at promoting self-determination, stimulating the design of evidence-based practices, since evaluation requires evidence (Schalock, 2018).…”
Section: Discussionmentioning
confidence: 99%